Café com arte contemporânea: tramas e poéticas para as artes visuais no Ensino Médio - MARTINS, Evarista Barbosa Guimarães (2020)
We present research that aims to improve the teaching and learning of contemporary visual art in high school. The general objective of the research project Coffee with Contemporary Art: Plots and Poetics for Visual Arts in High School will be to improve the teaching process learning the contemporary visual art from the dialogue between local visual artists and students. Empowering the reflection on the diversity of languages, materialities and themes of contemporary artistic production. We used the participatory action research methodology, in a qualitative / quantitative approach, exploratory-descriptive line, based on data collection procedures, through questionnaires reports of experiences with students. The research subjects will be students from Cidade Operária I High School Center, on the outskirts of São Luís. The research project is divided into stages where initially readings of texts, presentation of printed images and video will be addressed, where the conceptualization will be addressed. art, contemporary aesthetics, life and works of local visual artists. Visits to exhibitions in art galleries and / or cultural centers of contemporary art and meetings with local visual artists in school. It should last six months, culminating in plastic works productions where students will have the opportunity to elaborate poetic projects that will be presented throughout the research for the school and family community.